Listed firm's level of stakeholder transparency: The comply or explain evidence from the Danish corporate governance code - Caspar Rose (International Journal of Business Science & Applied Management (IJBSAM), 2015)
This article analyzes how Danish listed firms comply with the Danish Corporate Governance Code's recommendations regarding the categories: Role of shareholders, role of stakeholders and transparency. It is shown that the number of recommendations can be explained by six different underlying factors which account for the vast majority of the variation. The analysis reveals that the official classification of the three different sections in the Danish corporate governance must be abandoned. It is interesting to note that even though the "comply or explain" principle assumes that a meaningful explanation is equally good as compliance - the analysis documents that the vast majority of the firms complies with the recommendations. The article introduces a new methodology to measure the degree of compliance within these specific areas. This categorization serves as input for a multivariate analysis that explores how the different recommendations covariate as well as can be placed into distinct discrete groups. The policy implication is that future code revisions should rely on a multivariate approach when seeking to classify and structure the different code sections regarding the firm's stakeholders. Otherwise, there is a risk that board members may associate a large number of recommendations as mechanistic "tick the box" exercises, which does not add value.
Keywords: 650; corporate governance; transparency; compliance; comply or explain; factor and cluster analysis